Ice island - Shahan, Sherry (Delacorte Press, 2012)
Thirteen-year-old Tatum's dream of competing in the grueling 1,049-mile Iditerod Trail Sled Dog Race may be at an end when she becomes lost in a freak snowstorm during a training run on Alaska's remote Santa Ysabel Island.